2010
DOI: 10.1029/2010ja015395
|View full text |Cite
|
Sign up to set email alerts
|

Drift shell bifurcation near the dayside magnetopause in realistic magnetospheric magnetic fields

Abstract: [1] We study trapped energetic particles in the terrestrial magnetosphere undergoing drift shell bifurcation in the magnetic field lacking north-south and east-west symmetry. Drift shell bifurcation occurs near the dayside magnetopause, where, due to the solar wind compression, the field strength has a local maximum near the equatorial plane. As a result, a charged particle may become temporarily trapped in one of the hemispheres while traversing the region. Although this phenomenon has been known for a long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 25 publications
1
21
2
Order By: Relevance
“…This contradicts the conclusions of Wan et al [2010], who suggested that the dominant effect is caused by the east-west asymmetry in the magnetic field which produces large adiabatic (independent of the bounce phase) changes in the invariant. To validate our qualitative conjecture we ran the following numerical experiments illustrated in Figures 5 and A2a.…”
Section: The Structure and Mechanics Of Drift Orbit Bifurcationscontrasting
confidence: 54%
See 4 more Smart Citations
“…This contradicts the conclusions of Wan et al [2010], who suggested that the dominant effect is caused by the east-west asymmetry in the magnetic field which produces large adiabatic (independent of the bounce phase) changes in the invariant. To validate our qualitative conjecture we ran the following numerical experiments illustrated in Figures 5 and A2a.…”
Section: The Structure and Mechanics Of Drift Orbit Bifurcationscontrasting
confidence: 54%
“…[13] We first determine the extent of drift orbit bifurcations in the outer electron belt. The range of drift shells affected by bifurcations depends on the solar wind and geomagnetic conditions controlling the geomagnetic field [Wan et al, 2010]. Bifurcations are most sensitive to the value of the solar wind dynamic pressure (P dyn ), which controls the daynight asymmetry of the field.…”
Section: The Extent Of Drift Orbit Bifurcationsmentioning
confidence: 99%
See 3 more Smart Citations